Pengaruh Media Animasi Audio Visual Terhadap Hasil Belajar Siswa di SD Negeri 68 Palembang - Baiti, Rahmi; Yulaini, Erma; Laksana, Robert Budi (PPSDP Undergraduate Journal of Educational Sciences, 2025)
The results of initial observations and discussions before the research with the fourth grade teacher at SD Negeri 68 Palembang in the learning process were still a lack of student understanding in understanding the learning material which resulted in low student learning outcomes, but the learning process was less interactive and varied. The problem in this research is whether there is an influence of audio-visual animation media on student learning outcomes at SD Negeri 68 Palembang. The aim of this research is to determine the effect of audio-visual animation media on student learning outcomes at SD Negeri 68 Palembang. This research uses a true-experimental design with the form of a pretest-posttest control group design, where two groups are selected at random and then given a pretest to determine whether there are initial and final conditions between the two experimental groups and the control group. Based on the learning outcomes shown in the posttest results, the control class obtained an average score of 61.90 and the experimental class obtained an average score of 77.61. So, it can be said that the experimental class which was given treatment using audio-visual animation media was above the KKM, namely 70 and was declared complete. Meanwhile, the control class has not been able to reach the KKM.